Learning calculus through PBL in an industrial engineering and management program-a seven-year study - Cargnin-Stieler, Marinez (2019)
This paper aims to study ways of contributing to the development of Calculus through a Project-Based Learning (PBL) approach, which involves students in their first semester of the Integrated Master's program in Industrial Engineering and Management (IEM) at the University of Minho. The study presents the analysis of forty-two interdisciplinary project reports developed by students over a seven-year period. The reports offer good evidence for the application of the requested Calculus learning outcomes, demonstrating that the application of Calculus content occurred during the development of the project. This finding means that PBL was successful as a truly active learning process for Calculus that involves students learning independently through the interdisciplinary resolution of problems related to their engineering professional profiles.